2021
DOI: 10.1111/conl.12783
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the intensity of conflicts in conservation

Abstract: Conflicts between the interests of biodiversity conservation and other human activities pose a major threat to natural ecosystems and human well-being, yet few methods exist to quantify their intensity and model their dynamics. We develop a categorization of conflict intensity based on the curve of conflict, a model originally used to track the escalation and deescalation of armed conflicts. Our categorization assigns six intensity levels reflecting the discourse and actions of stakeholders involved in a given… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 39 publications
(53 reference statements)
0
15
0
Order By: Relevance
“…In a recent study, Straka et al (2020) found that photographs of vulnerable and distressed bats might be an important tool to temporarily increase people's emotional reactions to bats, their wildlife value orientation and probably, more importantly, their support for bat conservation. These findings illustrate the relevance of information to promote animal conservation and highlight the relevance of developing effective communication campaigns based on scientific findings (Cusack et al 2021;Lu et al 2021;MacFarlane & Rocha 2020).…”
Section: Discussionmentioning
confidence: 60%
“…In a recent study, Straka et al (2020) found that photographs of vulnerable and distressed bats might be an important tool to temporarily increase people's emotional reactions to bats, their wildlife value orientation and probably, more importantly, their support for bat conservation. These findings illustrate the relevance of information to promote animal conservation and highlight the relevance of developing effective communication campaigns based on scientific findings (Cusack et al 2021;Lu et al 2021;MacFarlane & Rocha 2020).…”
Section: Discussionmentioning
confidence: 60%
“…Riley et al (2018) examined trust in wildlife agencies and identified that trust was greater when personnel actions created a sense of fairness for stakeholder involvement. Extremely positive (or negative) messaging meanwhile may have the opposite effect, with a risk of more organised opposition and resulting conflict escalation (Cusack et al 2021;Niemiec et al 2020a, b). There may always be issues affecting trust (Riley et al 2018), but investment in trust-building and incorporating stakeholder viewpoints will mean it is more likely that conflicts can be negated and coexistence achieved for both reintroduced and already present species (Bennett et al 2017;Coz and Young 2020;Redpath et al 2015;Riley et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the income generated from, and the land allocated to, leopard trophy hunting may improve conservation efforts and aid in the recovery of declining populations (Palazy et al, 2011; Swanepoel et al, 2014). Tolerance may therefore be crucial to their survival in unprotected areas (Power et al, 2021), where growing human population densities may lead to increased human–wildlife conflict (Croes et al, 2011; Cusack et al, 2021; Redpath et al, 2013; Swanepoel et al, 2014). Trophy hunting and its economic benefits might also then serve as an incentive for both the maintenance of trophy species and the protection of their habitats (i.e., as both umbrella and sentinel species), making hunters proponents of conservation (Palazy et al, 2011).…”
Section: Introductionmentioning
confidence: 99%